Tannic acid mitigates salmonella-induced lung injury via gut-lung axis in broilers - Aoao Wu; Liu Xu; Yinzhu Zhang; Yuanyuan Zhu; You Wu; Jing Wu; Lixin Wen; Zhihang Yuan; Ji Wang (Poultry Science)
Tannic acid (TA), a polyphenolic compound derived from plants, exhibits anti-inflammatory, antibacterial, antiviral, and antioxidant biological activities. Salmonella, a prevalent foodborne pathogen, poses a significant threat to poultry, resulting in considerable economic losses for the animal husbandry industry. In this study, we investigated the protective effects of TA against lung and intestinal injuries induced by a transient Salmonella infection in broilers. After a ten-day infection period, although Salmonella was not detected in the intestinal content of broilers, the infected broilers exhibited reduced body weight and compromised intestinal barrier function. Salmonella infection facilitated the growth of detrimental bacteria in the lungs and ileums, triggering an inflammatory response. TA inhibited the pathogen's colonization in the lungs and reduced serum levels of lipopolysaccharide (LPS) as well as lung levels of myeloperoxidase (MPO). Moreover, TA down-regulated the expression of pro-inflammatory cytokines and hindered the polarization of M1 macrophages in the lungs.In summary, TA mitigates Salmonella-induced lung inflammation and immune imbalance by its anti-inflammatory, antioxidant and antibacterial properties in broilers.